Diagnosing non-cavitated lesions in epidemiological studies: practical and scientific considerations - Joana Christina Carvalho; Heliana Dantas Mestrinho (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Over the last decade, there has been growing interest in diagnosing non-cavitated lesions in epidemiological studies involving large numbers of preschool children, schoolchildren and young adults. In this context, assessment of lesions characteristics indicating whether or not there is ongoing mineral loss is also considered relevant. The reasoning sustained by these studies is that diagnosis of the caries process limited to the cavitated level is no longer in accordance with current state-of-the-art knowledge in cariology. This paper highlights one topic of the lecture entitled "Caries Process: Evolving Evidence and Understanding," presented at the 18th Congress of the Brazilian Association for Oral Health Promotion (Associação Brasileira de Odontologia de Promoção de Saúde - ABOPREV) in April 2013. In the framework of epidemiological studies, the interest in diagnosing active and inactive non-cavitated lesions was elucidated. However, relevant questions associated with the diagnosis of non-cavitated lesions that might raise concerns among researchers and health administrators were not addressed. The present paper aims to bring these questions into discussion. The contribution of this discussion in terms of developing the understanding of caries decline is analyzed by using data from a caries trends study of Brazilian preschool children residing in the Federal District of Brazil as an example. The inclusion of active and inactive non-cavitated lesions in the diagnosis of the caries process allowed us to demonstrate that, in Brazilian 1- to 5-year-old children, caries prevalence decreased significantly from 1996 to 2006, simultaneously with a reduction in the rate of caries progression.